Defective removal of invariant chain peptides from MHC class II suppresses tumor antigen presentation and promotes tumor growth - Joanna Bandola-Simon; Yoshinaga Ito; Kai W. Wucherpfennig; Paul A. Roche (Cell Reports)
Summary: Tumor-draining lymph node dendritic cells (DCs) are poor stimulators of tumor antigen-specific CD4 T cells; however, the mechanism behind this defect is unclear. We now show that, in tumor-draining lymph node DCs, a large proportion of major histocompatibility complex class II (MHC-II) molecules retains the class II-associated invariant chain peptide (CLIP) fragment of the invariant chain bound to the MHC-II peptide binding groove due to reduced expression of the peptide editor H2-M and enhanced activity of the CLIP-generating proteinase cathepsin S. The net effect of this is that MHC-II molecules are unable to efficiently bind antigenic peptides. DCs in mice expressing a mutation in the invariant chain sequence that results in enhanced MHC-II-CLIP accumulation are poor stimulators of CD4 T cells and have diminished anti-tumor responses. Our data reveal a previously unknown mechanism of immune evasion in which enhanced expression of MHC-II-CLIP complexes on tumor-draining lymph node DCs limits MHC-II availability for tumor peptides.